Bio-guided Fractionation of Centaurea bruguierana subsp. belangeriana Extract Based on Anti-Helicobacter pylori Activity - mahdieh kalkhorani; Abbas Hadjiakhoondi; Narguss Yassa; Mohsen Amin; Seyedeh Bahareh Damankash; Fatemeh Moradkhani; Mahdi Vazirian* (Iranian Society of Pharmacognosy, 2019)
Background and objectives: Centaurea bruguierana subsp. belangeriana (DC.) Bornm. is an annual herb widely distributed in the world. It is used in folk medicine of Iran as an anti-ulcer for gastrointestinal problems. Previous studies have revealed the anti-ulcer effects of the plant extract and in the present study the anti-Helicobacter pylori activity of different fractions, isolated from C. bruguierana subsp. belangeriana was evaluated. Urease and motility inhibition activity were also examined for determination of possible mechanisms. Method: Ethanol 80% was used for the extraction. Chloroform, ethyl acetate, and methanol fractions of the total extract were obtained by solid-liquid extraction. All extracts were evaluated against jack bean urease, bacterial swarming and Minimal Inhibitory Concentrations (MICs) were determined using the agar diffusion method. Bio-guided fractionation was performed by isolation and purification of compounds from active fractions using silica-gel open column chromatography by column and thin layer chromatographic methods and identification by spectroscopic data. Results:  Total extract and chloroform fraction possessed the highest anti-H. pylori activity with MIC 325 300 µg/mL and, respectively. The total extract was the most potent urease inhibitor (IC50 250 µg/mL). The motility test confirmed the results by inhibiting swarming at concentrations comparable with IC50. The separation and purification of effective compounds of the chloroform extract was performed according to the results; Lupeol (1), Retusin (2), and Apigenin (3) were isolated and identified. Conclusion: Our research demonstrated a noticeable anti-H.pylori activity of different fractions fromC.bruguierana subsp. belangeriana especially the nonpolar fraction.